2004
DOI: 10.1136/jmg.2004.018234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a cancer genetics education programme on clinician knowledge and practice

Abstract: Background: Many clinicians lack adequate knowledge about emerging standards of care related to genetic cancer risk assessment and the features of hereditary cancer needed to identify patients at risk. Objective: To determine how a clinical cancer genetics education programme for community based clinicians affected participant knowledge and changed clinical practice. Methods: The effects of the programme on participant knowledge and changes in clinical practice were measured through pre and post session knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 33 publications
0
22
1
Order By: Relevance
“…These findings contribute to studies demonstrating the value of educational interventions in hereditary cancer (Blazer et al 2004;Carroll et al 2009Carroll et al , 2011Houwink et al 2013Houwink et al , 2014aSchroy et al 2005;Watson et al 2001). Watson showed improved referral decisions for patients with a FH of breast/ovarian cancer, using mailed information including a laminated summary card with simple referral guidelines, a booklet with more detailed information, and two patient leaflets (Watson et al 2001).…”
Section: Discussionmentioning
confidence: 57%
“…These findings contribute to studies demonstrating the value of educational interventions in hereditary cancer (Blazer et al 2004;Carroll et al 2009Carroll et al , 2011Houwink et al 2013Houwink et al , 2014aSchroy et al 2005;Watson et al 2001). Watson showed improved referral decisions for patients with a FH of breast/ovarian cancer, using mailed information including a laminated summary card with simple referral guidelines, a booklet with more detailed information, and two patient leaflets (Watson et al 2001).…”
Section: Discussionmentioning
confidence: 57%
“…While participant satisfaction is important, we did not collect data regarding the accuracy of the information being given to participants by their OHCPs. Previous reports regarding primary care physicians' knowledge about genetic testing for hereditary cancers have found a lack of proficiency in this area [22][23][24][25][33][34][35][36]. Although The American Society of Clinical Oncology has provided continuing education for oncologists in the area of cancer genetic risk assessment and testing [37], efforts to educate OHCPs should continue and preferred methods of learning about genetic information should be identified.…”
Section: Discussionmentioning
confidence: 97%
“…However, many studies have shown that even practicing physicians lack adequate knowledge about important concepts regarding hereditary cancer syndromes [11][12][13][14][15][16]. Furthermore, there is very little information about medical residents' knowledge of hereditary cancer syndromes and the effectiveness of educational programs designed to improve cancer genetics knowledge [17,18]. Therefore, the objective of this study was to assess obstetrics/ gynecology residents' family history documentation practices and knowledge of HBOC and Lynch syndrome in order to determine areas of deficiency to establish future targeted education programs.…”
Section: Introductionmentioning
confidence: 99%